Simulation, bifurcation, and stability analysis of a SEPIC converter controlled with ZAD - Aquiles J. Morelo; Simeón Casanova Trujillo; Fredy E. Hoyos (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This article presents some results of SEPIC converter dynamics when controlled by a center pulse width modulator controller (CPWM). The duty cycle is calculated using the ZAD (Zero Average Dynamics) technique. Results obtained using this technique show a great variety of non-linear phenomena such as bifurcations and chaos, as parameters associated with the switching surface. These phenomena have been studied in the present paper in numerical form. Simulations were done in MATLAB.